Cancer/Testis Antigens as Biomarker and Target for the Diagnosis, Prognosis, and Therapy of Lung Cancer - Yang, Ping; Qiao, Yingnan; Meng, Mei; Zhou, Quansheng (Frontiers in Oncology, 2022)
Lung cancer is the leading type of malignant tumour among cancer-caused death worldwide, and the 5-year survival rate of lung cancer patients is only 18%. Various oncogenes are abnormally overexpressed in lung cancer, including cancer/testis antigens (CTAs), which are restrictively expressed in the male testis but are hardly expressed in other normal tissues, if at all. CTAs are aberrantly overexpressed in various types of cancer, with more than 60 CTAs abnormally overexpressed in lung cancer. Overexpression of oncogenic CTAs drives the initiation, metastasis and progression of lung cancer, and is closely associated with poor prognosis in cancer patients. Several CTAs, such as XAGE, SPAG9 and AKAP4, have been considered as biomarkers for the diagnosis and prognostic prediction of lung cancer. More interestingly, due to the high immunogenicity and specificity of CTAs in cancer, several CTAs, including CT45, BCAP31 and ACTL8, have been targeted for developing novel therapeutics against cancer. CTA-based vaccines, chimeric antigen receptor-modified T cells (CAR-T) and small molecules have been used in lung cancer treatment in pre-clinical and early clinical trials, with encouraging results being obtained. However, there are still many hurdles to be overcome before these therapeutics can be routinely used in clinical lung cancer therapy. This review summarises the recent rapid progress in oncogenic CTAs, focusing on CTAs as biomarkers for lung cancer diagnosis and prognostic prediction, and as targets for novel anti-cancer drug discovery and lung cancer therapy. We also identify challenges and opportunities in CTA-based cancer diagnosis and treatment. Finally, we provide perspectives on the mechanisms of oncogenic CTAs in lung cancer development, CTAs as biomarkers for lung cancer diagnosis and prognostic prediction, and CTAs as a new platform for discovering novel therapeutics against lung cancer and various other types of malignant tumours.